2016
DOI: 10.35119/maio.v1i2.24
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of aqueous humor flow and intraocular pressure under uncertainty: towards individualized glaucoma management

Abstract: Purpose: The aim of the proposed analysis is to provide both a qualitative description and a quantitative assessment of how variations in aqueous humor (AH) flow parameters influence intraocular pressure (IOP) and the outcome of IOP-lowering medications.Methods: We developed a mathematical model that describes the steady-state value of IOP as the result of the balance between AH production and drainage. We performed stochastic simulations to assess the influence of different factors on the IOP distribution in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Finally, no specific altitude was consistently utilized across studies, therefore complicating the understanding of what elevation level is required to significantly impact IOP and/or ocular hemodynamics. In order to overcome these limitations, in this study, we used an innovative methodological approach indicated as physiology-enhanced data analytics able to integrate experimental data-derived from the MBS [32]-with validated mathematical models [39,40] in order to shed further light on the physiologic relationships between IOP, BP, and ocular hemodynamics with altitude.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, no specific altitude was consistently utilized across studies, therefore complicating the understanding of what elevation level is required to significantly impact IOP and/or ocular hemodynamics. In order to overcome these limitations, in this study, we used an innovative methodological approach indicated as physiology-enhanced data analytics able to integrate experimental data-derived from the MBS [32]-with validated mathematical models [39,40] in order to shed further light on the physiologic relationships between IOP, BP, and ocular hemodynamics with altitude.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also used the mathematical model validated in [40] on AH dynamics in combination with the experimental data from the MBS to shed further light on the physiological mechanisms between changes in IOP and BP with altitude through two sub-analyses. The pe-IOP analysis used the values of MAP derived from the MBS as individualized inputs and provided the corresponding IOP values at different altitudes as individualized outputs, which were then compared with the actual IOP values collected in the real word (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations